2018
DOI: 10.2147/jmdh.s174198
|View full text |Cite
|
Sign up to set email alerts
|

mHealth for diabetes self-management in the Kingdom of Saudi Arabia: barriers and solutions

Abstract: PurposeIn this paper I present a perspective of mobile health (mHealth) technologies for diabetes in conjunction with an overview of the current status of mHealth technologies for diabetes self-management and the clinical evidence in the Kingdom of Saudi Arabia. In addition, a small survey to identify the barriers to mHealth for diabetes care in the Kingdom and the relevant solutions are discussed.Participants and methodsIn order to study the relevant obstacles for adopting mHealth solutions for diabetes care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Further, patient education interventions should include programs that improve patient’s health literacy, which was demonstrated to improve compliance in self-care activities [ 30 ]. Other strategies used technology-based solutions, such as the usage of smartphone applications and gamification, to alleviate further obstacles to self-management and produce promising results in the Kingdom [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, patient education interventions should include programs that improve patient’s health literacy, which was demonstrated to improve compliance in self-care activities [ 30 ]. Other strategies used technology-based solutions, such as the usage of smartphone applications and gamification, to alleviate further obstacles to self-management and produce promising results in the Kingdom [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, increasing attention is given to diabetes self-management, with several pieces of research carried out locally, showing inadequate levels of practice in various dimensions of self-care [ 12 - 14 ]. Such observations prompted physicians’ and researchers’ efforts to promote patient education for self-care [ 15 - 16 ] and to propose technology-based solutions such as usage of smartphone applications and gamification of self-care behavior to alleviate further obstacles and produce promising results in the Kingdom [ 17 - 18 ]. On the other hand, national data remain scarce, stressing the need for the continuous monitoring of self-management among patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies that surveyed the usage patterns and preferences of people using health apps were conducted among specific populations and not among patients with diabetes or any other chronic diseases . A survey on barriers to mHealth implementation in Saudi Arabia found that mHealth expertise and human shortage; funding and infrastructure investments; legal, privacy standardization and regulatory obstacles and bureaucracy are the hurdles in bringing the mHealth technology …”
mentioning
confidence: 99%
“…17,18 A survey on barriers to mHealth implementation in Saudi Arabia found that mHealth expertise and human shortage; funding and infrastructure investments; legal, privacy standardization and regulatory obstacles and bureaucracy are the hurdles in bringing the mHealth technology. 19 The mobile usage pattern was also found to vary rapidly with the continuous emergence of newer technologies, particularly with the easier availability of high-speed mobile broadband technologies, such as 3G and 4G. Therefore, information regarding patterns of usage, user preferences, and the difficulties faced by patients is greatly necessary in order to initiate any mHealth related applications within a healthcare setting.…”
mentioning
confidence: 99%
“…Presenting these statistics, Alanzi (2018) noted that policy deficits and scarce research on e-Health systems for diabetes have resulted in its poor implementation at hospital level. The e-Health initiatives of the Saudi Ministry of Health were limited to creating silos of health records and some service facilitations [3]. There had been only some very recent works on this issue in Saudi Arabia like those of Aldahmash, Ahmed, Qadri, Thapa, and AlMuammar (2019) and Belcher, Vess, and Johnson (2019) [4] [8].…”
Section: What Are the Modelling System Requirements For E-health In Saudi Arabia?mentioning
confidence: 99%